Digital Therapeutics for Type 2 Diabetes Management: A Systematic Review of Mobile and Web-Based Interventions for Improving Glycemic Control and Patient Engagement - Khalid, Rimsha; Khalid, Abeera; Khaliq, Izza; Awan, Misbah Farooq; Ashraf, Ahmad Bilal; Ayub, Zawar (Indus Journal of Bioscience Research, 2024)
Background: Type 2 diabetes mellitus (T2DM) is a chronic condition that is common and affects millions worldwide creating an immense burden to the healthcare system. Although traditional management strategies are effective, they unfortunately do tend not to adhere well. Given the rise of digital therapeutics, we rejoice in the arrival of innovative, scalable, and personalized solutions for glycemic control and patient engagement. Aim: This systematic review aims to evaluate the effectiveness of mobile or web-based digital therapeutic interventions that are targeted to improve patients’ glycemic control and engagement with their T2DM. Methodology: Systematic review of peer-reviewed studies published between the years 2015 and 2023 followed PRISMA guidelines. Interventions that improved glycemic control and engagement in the adult T2DM population were included, with diverse methodologies (including RCTs, cohort studies). HbA1c and patient engagement metrics were our primary outcomes, along with behavioral and lifestyle modifications among other secondary outcomes. Results: The inclusion criteria were met by seven studies that showed reductions in HbA1c levels of 0.4 to 1.2%, even more increases in patient satisfaction, and an increased rate of medication adherence. Interventions bearing both personalized feedback and real time support, as well as gamification improved glycemic control and maintained patient engagement. One obstacle was perceived variability in such digital literacy, and another was socioeconomic barriers. Conclusion: There is evidence that mobile and web based digital interventions can improve glycemic outcomes and patient engagement with T2DM. However, although much of their potential remains, it is important to do further research on accessibility and long term efficacy to maximize their influence across diverse populations.